Real-time Energy Management Method for Data Center Considering Shiftable Workload and Renewable Energy - Li, Feng; Zhang, Yinya; Xi, Jianghui; Liu, Yize; Yan, Mingyu (Recent Advances in Electrical & Electronic Engineering, 2025)
AimThis study aimed to improve the electricity economy of data centers.BackgroundData centers have been rapidly developed over the last decade to balance increasing computing workloads. Such a rapid development has been found to result in a significant increase in higher electricity expenses for data centers.ObjectiveThe objective of this study was to improve the operation efficiency of a data center by developing a data center energy management model considering shiftable data workloads, energy storage, and renewable energy.MethodsFirst, a data center workload model has been established to describe its temporal shifting characteristics. Then, a data center power consumption model has been developed to describe the energy usage of IT equipment and cooling systems. Finally, the energy management model for the data center has been developed to reduce the electrical energy costs of the data center.ResultsCase studies have been performed on a trial system to illustrate the validity of the proposed model, which has been found to meet the requirements.ConclusionRationally re-scheduling the delay-tolerant workloads and making full use of energy storage can enhance the flexibility of the power system and reduce electricity costs by 19.06%.
Keywords: reduce electircity costs